Coupling Coordination Analysis of Natural Resource Utilization Benefits in Beijing From 1978 to 2018 - Yin, Ziyan; Zhao, Chunjiang; Liu, Yu; Pan, Yuchun; Zhou, Wei (Frontiers in Environmental Science, 2022)
With the acceleration of economic and social development, the demand for natural resources has increased. In order to realize the sustainable utilization of natural resources (SUNRs), it is necessary to seek ways to improve the natural resources utilization benefits (NRUBs) and promote the coordinated development of economic, social and ecological benefits. This paper explores the coupling coordination relationships of NRUBs in Beijing from 1978 to 2018 and analyzes the influencing factors. We first establish a comprehensive evaluation index system covering economic, social and ecological benefits to quantify NRUBs. Then, a coupling coordination degree (CCD) model is applied to reveal the evolution characteristics of the coupling coordination relationships among the NRUBs system. Finally, the main factors affecting the coordinated development of NRUBs are identified through grey relational analysis (GRA). Three main results are found as follows. (1) From 1978-2018, the economic, social, ecological and comprehensive benefits all have been greatly improved, though with some fluctuations. (2) The coupling coordination relationships of NRUBs show upward trends during the study period, and their coordination types transform from imbalance to coordination. (3) Urbanization, industrial structure, technology innovation, economic development and environmental awareness all have significant impacts on the coupling coordination relationships of NRUBs. This paper can provide a reference for other comprehensive evaluation of natural resources and the formulation of natural resources utilization policies.